A new elasmosaurid specimen from the upper Maastrichtian of Antarctica: new evidence of a monophyletic group of Weddellian elasmosaurids - O'gorman, Jose Patricio; Coria, Rodolfo Anibal (Alcheringa: An Australasian Journal of Palaeontology)
A new fossil elasmosaurid specimen, MLP 15-I-7-48, from the upper Maastrichtian Sandwich Bluff Member of the López de Bertodano Formation, Vega Island, Archipelago James Ross, Antarctica, is described. The fossil is a well-preserved anterior limb, which shares with Vegasaurus molyi from the upper Maastrichtian of Antarctica, a concave to flat anterior margin of the humeral shaft, and with Vegasaurus molyi and Aphrosaurus furlongi from the upper Maastrichtian of California, a well-defined depression on the anterior margin of the ventral surface of the humeral shaft. A phylogenetic analysis recovered MLP 15-I-7–48 as sister group of the lower Maastrichtian Vegasaurus molyi within a new clade nominated as Weddellonectia: Kawanectes lafquenianum ((Vegasaurus molyi; MLP 15-I-7–48) (Morenosaurus stocki (Aristonectinae))). This indicates that the previously proposed faunal turnover between the early and late Maastrichtian Weddellian marine reptile fauna, did not severely affect the non-aristonectine elasmosaurids. Additionally, other taxa previously considered evidence of a faunal turnover are re-evaluated. Fil: O'gorman, Jose Patricio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Coria, Rodolfo Anibal. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina